EDUKASI DAN SKRINING ANEMIA PADA REMAJA PUTRI DALAM UPAYA PENCEGAHAN STUNTING - Fitriani Umar; Nur Hafizah; Nurfardianty A.R. Amrah; Dhea Ananda Putri; Hikma Hikma; Fadillah Sudirman; Khusnul Khotimah; Nur Sadilah; Fadwandi Suganra (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
The prevalence of stunting is still quite high. Specific nutritional interventions to prevent stunting are carried out from preconception age, especially in preventing anemia and women of childbearing age having normal nutritional status. The aim of this activity is to provide education and screen nutritional status for young women. The activity was carried out at SMKN 7, Suppa District, Pinrang Regency. Activities are carried out by providing education about anemia, symptoms, cut off points for someone who is said to have anemia and how to prevent and overcome it. In this activity, nutritional status was also measured in the form of checking Hb levels and upper arm circumference in class IX female students. Students' knowledge before and after education was measured using a questionnaire. The results of the implementation of the activity showed an increase in female students' knowledge regarding anemia and from the results of measuring nutritional status it was found that 5% of teenagers experienced anemia and 33.3% experienced chronic energy deficiency (KEK). It is hoped that there is a need for ongoing education to teenagers, especially regarding anemia and also about the importance of consuming Fe tablets. Monitoring to regularly consume the Fe tablets that have been given also needs to be done to prevent teenagers from experiencing anemia